Arduino up and running - Jepson, Brian, 1967-; Safari eBooks ([S.l.] : O'Reilly Media, 2010)
"Build fun and creative electronic projects with Arduino, the open source prototyping platform that's taken the design and hobbyist world by storm. In 90 minutes of video, you'll get a complete overview of basic electronics and the Arduino microcontroller and software. Then you'll follow hands-on lessons on how to write simple Arduino programs that interact with various electronic components. This easy-to-follow tutorial is ideal for designers, artists, hackers, makers, and anyone interested in creating sensor-based systems"--Resource description page (viewed Jan. 20, 2011).
System requirements: Adobe Flash Player, version 8 or higher.
Title from title screens (viewed Jan. 20, 2011).
Publication information from resource description page (viewed Jan. 20, 2011).
Presenter, Brian Jepson.
Keywords: Arduino; Science projects -- Design and construction; Open source software; Electronics -- Data processing; Prototypes, Engineering; Electronic books